Analisis Hukum Islam Tentang Perkembangan Financial Technology (Fintech) - Wati, Ai; Padilah, Umi; Setiawan, Deri (STAI Al Musaddadiyah Garut, 2024)
The emergence of fintech as a necessity in today’s digital era does not contradict Islamic law. Fintech refers to companies that combine financial services with technology. The rapid advancement of technology has contributed to significant developments in the financial sector, which is evident in the rise of fintech. Fintech provides various benefits to society, particularly in financing, such as business capital or the sustainability of their ongoing businesses. This gives rise to key research questions: How does fintech improve societal welfare through modern technology, and what is the Islamic legal perspective on fintech? The objectives of this study are to determine how fintech improves societal welfare through modern technology and to analyze the application of Islamic law to fintech. The research method employed is a qualitative library research approach. Through this qualitative approach, the study examines Islamic legal analysis regarding the development of financial technology (fintech) and its compliance with Sharia economic principles. The findings of this research indicate that, from an Islamic legal perspective, fintech has shown significant developments, and various analyses have been conducted on the application of Sharia principles within this industry. Therefore, this study concludes that fintech does not conflict with Islamic financial principles as long as it adheres to Sharia regulations. Keywords: Islamic Law, Financial Technology